Nikolaj Kempf in njegova mistična teologija - Bobovnik, Nena (Primerjalna književnost, 2018)
The first to write about mysticism on the territory of today's Slovenia was a Carthusian monk Nicholas Kempf from Straßburg (c. 1416-1497). He studied in Vienna, entered the Carthusian monastic order at the charterhouse of Gaming, and lived in today's Slovenia for twenty-one years as prior at Jurklošter (Geirach) and Pleterje (Pletriach). The first part of the article focuses on his life and work, taking into account mostly his three mystical volumes (Tractatus de mystica theologia, De ostensione regni Dei and Explanatio in Cantica canticorum), which were held in a manuscript (Nicolaus Kempf: Opera varia, Ms. 262) at the charterhouse of Seitz. The second part strives to take the first step towards the explanation of Kempf's mystical theology, which he sees as the purpose of all theology (finis tocius theologie). Another goals are to show the difference between speculative and affective theology, to explain Kempf's use of the medieval Rhineland-Flemmish mysticism's expressions abegescheidenheit and gelassenheit, and by doing so to demonstrate that in the fifteenth century its reception took place in today's Slovenia as well. Lastly, it arrives at the conclusion that Kempf was an unjustly overlooked author.
Keywords: mystical theology; Nikolaj Kempf, ok. 1416-1497; Carthusians; mistična teologija; affective theology; kartuzijani; afektivna teologija; Rhineland-Flemmish mysticism; rensko-flamska mistika; Gelassenheit; Abgeschiedenheit